Motivation and Job Satisfaction on The Performance of Health Workers at RSIA Aisyiyah Pekajangan - Putri, Aqmarlia Janita; Wardani, Ratna (Syntax Corporation, 2024)
Employee motivation and job satisfaction are important aspects in human resource management. Healthcare professionals must do their best as healthcare leaders. Therefore, it is very important to meet the needs of health workers and ensure job satisfaction. This research aims to quantify the impact of these variables and provide insights that can guide improvements in human resource strategies within healthcare organizations to enhance employee performance. This research is a quantitative research with a cross-sectional method. A sample of 127 respondents was obtained using Proportional Random Sampling. After filling in informed consent, respondents filled out motivation, satisfaction and performance questionnaires. After that, data processing and analysis was carried out using SPSS. The calculated F value is 13.212 > F table 3.92 and the sig is 0.000 < 0.05. From these results it can be said that simultaneously, the variables Motivation (X1) and Satisfaction (X2) influence the performance variable (Y). In the multiple liner regression test, the result was Y = 16.981 + 0.127X1 + 0.291X2 + e. Motivation and satisfaction have a significant effect on the performance of health workers.